PEMAKAIAN DIKSI DALAM PENULISAN CAPTION MEDIA SOSIAL INSTAGRAM - Maharani, Amanda (Diksi, 2020)
(Title: Usage of Diction in Writing of Social Media Caption Instagram).Communication often goes wrong either misunderstanding or offending. People who have a lot of vocabulary tend to communicate more easily. They know how to use the right diction according to the situation and conditions. The use of social media that is busy lately is widely used to express feelings of happiness, annoyance, disappointment or even anger. This is usually stated in the written status or caption. Indeed there are no provisions in the writing. However, users should be more careful to choose good and correct diction so as not to damage the existing language order. This study used a descriptive qualitative method with 32 PBB class of 5B class of PBSI students. The results obtained are the useof diction: (1) the use of Meaningful Denotation and connotation as many as 17 diction usage, (2) the use of popular words and study words as many as 8 diction usage, (3) the use of jargon, conversation words and slang as many as 16 diction usage, (4) the use of General Words and Special Words are 3 uses of diction, and (5) the use of the words Synonyms and Synchronized are 16 uses of diction. Based on these results it can be concluded that the use of the PBSI Student Class of 5B class 2017 in terms of politeness is quite good and can be accepted by the community.Keywords: diction, status, communication, social media